Reversible Pressure‐Dependent Mechanochromism of Dion–Jacobson and Ruddlesden–Popper Layered Hybrid Perovskites (Adv. Mater. 17/2022). Issue 17 (27th April 2022) - Muscarella, Loreta A.; Dučinskas, Algirdas; Dankl, Mathias; Andrzejewski, Michał; Casati, Nicola Pietro Maria; Rothlisberger, Ursula; Maier, Joachim; Graetzel, Michael; Ehrler, Bruno; Milić, Jovana V.
Abstract : Layered Hybrid Perovskites Mechanical pressure can be a tool for tailoring optoelectronic properties of layered hybrid perovskites without changing their composition. In article number 2108720, Bruno Ehrler, Jovana V. Milić, and co‐workers demonstrate that Dion–Jacobson and Ruddlesden–Popper perovskites based on 1, 4‐phenylenedimethylammonium and benzylammonium spacers show reversible mechanochromism in the 0–0.35 GPa pressure range due to a structural interplay between the organic spacer and the inorganic framework, expanding the perspectives for their future applications.